Carcass wrote:
If n is a positive integer, then \((4^n )^3\) is NOT equivalent to
(A) \(4^{3n}\)
(B) \(2^{6n}\)
(C) \(12^n \)
(D) \(64^n \)
(E) None of the above
An easy approach is to evaluate \((4^n )^3\) for a certain value of \(n\) and then plug that same value of \(n\) into the answer choices.
For example, if \(n = 1\), then \((4^n )^3 = (4^1 )^3 = (4)^3 = 64\)
Now that's plug \(n = 1\) into each answer choice...
(A) \(4^{3n} = 4^{3(1)} = 4^4 = 64\) ELIMINATE A
(B) \(2^{6n} = 2^{6(1)} = 2^6 = 64\) ELIMINATE B
(C) \(12^n = 12^1 = 12 \) Bingo!
Answer: C